2013
DOI: 10.1177/0748233713480206
|View full text |Cite
|
Sign up to set email alerts
|

The hazardous effects of three natural food dyes on developmental stages and longevity of Drosophila melanogaster

Abstract: Nowadays, food dyes obtained from herbal, animal, microbial and mineral sources are widely used as food additives. In this study, the toxic effects of three different natural food dyes (carmine, turmeric and annatto) on 72 ± 4 h larvae of Oregon-R wild type of Drosophila melanogaster were investigated. For this purpose, four different application doses (50, 75, 100, 125 mg mL(-1)) were chosen by means of preliminary studies. It was determined that larval mortality increased with increasing concentration in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…anti-microbial, antioxidants, polyphenols), however, some concerning results, mainly derived from animal and/or cell-based experimental studies, have recently emerged regarding several additives. For instance, nitrates/nitrites 24 26 , carrageenans 31 , glutamate 32 34 , bixin 35 , 36 , artificial sweeteners 21 , 37 40 , phosphates 41 , 42 , emulsifiers 43 46 , caramel 47 , tartrazine 48 , 49 and butylated hydroxyanisole/ butylated hydroxytoluene (BHA/BHT) 48 were previously linked to metabolic, gut microbiota or endocrine perturbations along with carcinogenic, inflammatory and/or oxidative stress effects. Also, in May 2021, following an updated evaluation, EFSA reviewed its position on titanium dioxide (TiO 2 ) and stated that this additive could no longer be considered as safe 22 , 50 52 .…”
Section: Introductionmentioning
confidence: 99%
“…anti-microbial, antioxidants, polyphenols), however, some concerning results, mainly derived from animal and/or cell-based experimental studies, have recently emerged regarding several additives. For instance, nitrates/nitrites 24 26 , carrageenans 31 , glutamate 32 34 , bixin 35 , 36 , artificial sweeteners 21 , 37 40 , phosphates 41 , 42 , emulsifiers 43 46 , caramel 47 , tartrazine 48 , 49 and butylated hydroxyanisole/ butylated hydroxytoluene (BHA/BHT) 48 were previously linked to metabolic, gut microbiota or endocrine perturbations along with carcinogenic, inflammatory and/or oxidative stress effects. Also, in May 2021, following an updated evaluation, EFSA reviewed its position on titanium dioxide (TiO 2 ) and stated that this additive could no longer be considered as safe 22 , 50 52 .…”
Section: Introductionmentioning
confidence: 99%
“…However, some concerning results, mainly derived from animal and/ or cell-based experimental studies, have emerged regarding several additives. For instance, nitrates/nitrites [21][22][23] , carrageenans 24 , glutamate [25][26][27] , bixin 28,29 , artificial sweeteners [30][31][32][33][34] , phosphates 35,36 , emulsifiers [37][38][39] , caramel 40,41 , titanium dioxide (TiO2) 42 , tartrazine 43,44 and butylated hydroxyanisole/butylated hydroxytoluene (BHA/BHT) 43 were previously linked to metabolic, gut microbiota or endocrine perturbations along with carcinogenic, inflammatory and/or oxidative stress effects. Besides, some experimental results suggest that different additives may interact (among themselves and/or with the food matrix) and thus lead to synergistic or antagonist effects, but few studies have been performed on this topic to-date [45][46][47][48][49][50] .…”
mentioning
confidence: 99%
“…Our findings corroborate the role of turmeric in shortening lifespan from previous studies (Fig 1a). For instance, Uysal et al, (2015) found that turmeric shortened lifespan in D. melanogaster adults. Similarly, Hellfeld et al, (2023) found that increasing turmeric concentration in the diet decreased oviposition in adult females and subsequently reduced egg-to-adult viability in the developing larvae in D. malanogaster.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggest that (1) diet is a major ecological factor determining development and health of insects, (2) diet modulates the toxicity effects of chemical baits as well as (3) natural toxic compounds. To date, however, we have very little understanding of how diet and natural toxic compounds interact, most of which comes from the work in model species such as D. melanogaster (see e.g., Hellfeld et al, 2023;Raje et al, 2015;Uysal et al, 2015;Damalas, 2011, De Souza Tavares et al, 2016.…”
Section: Introductionmentioning
confidence: 99%